Actualización y manejo práctico de colitis ulcerosa - Gompertz G., Macarena; Sedano M., Rocío (Revista Hospital Clínico Universidad de Chile, 2018)
Ulcerative colitis (UC) is an autoimmune inflammatory chronic disease, which compromises the colonic mucosa continuously, affecting the rectum with a variable proximal extension to the cecum, in a relapsing and remitting way. The higher incidences and prevalence are described in Europe and North America, with no precise epidemiologic data from Chile. It usually presents in young patients with bloody diarrhea, with the diagnostic confirmation made by colonoscopic and histologic studies. There is no definitive cure for this condition, but the aim of the treatment is symptom resolution and endoscopic mucosal healing, based in the early use of 5-aminosalicylic acid drugs, steroids for a crisis, immunosuppressants, with some patients requiring biologic agents to reach remission. In some cases, colectomy is the last source for refractory disease or for treating colonic neoplasia. This review focuses on practical management of UC.